DYADIC CHANGES IN WELL-BEING ACROSS THE TRANSITION TO SENIOR HOUSING FACILITIES: A PROSPECTIVE LONGITUDINAL STUDY. (20th December 2022) - Luong, Gloria; Russell, Andrea; Miller, James
Abstract: Previous research examining the transition into senior housing has focused primarily on individuals and has used cross-sectional, retrospective designs after older adults have already moved into the facilities. These designs cannot disentangle changes over time and how partners influence this process. The Relocation and Transitional Experiences (RELATE) study leverages a prospective longitudinal design that tracked 157 participants (97 who participated in the study as part of a dyad with a romantic partner or other close partner (family member)) prior to moving into senior housing and across 3.5 months after the move. Participants ranged between 40-95 years of age. Results showed that those who were unmarried reported fewer depressive symptoms, but also less social support and lower life satisfaction than married participants. Changes over the 3.5 month period in depressive symptoms, social support, and rumination also varied by age. This study suggests partners may influence one another's developmental health trajectories.